Chemical Intolerance in Patients With Nasal Inflammatory Disorders Using QEESIâ“’ - Kwon, Byung Woo; Bae, Woo Yong; Jung, Nam Yoon; Lee, Chang Bae; Kim, Daeyeon (Archives of Clinical and Biomedical Research, 2019)
Background: In some of the inflammatory disorders, such as chronic rhinosinusitis (CRS), non-allergic rhinitis (NAR), or allergic rhinitis (AR), environmental agents can incite or exacerbate the symptoms of each disease. The aim of the study was to investigate the relationship of chemical intolerance in the nasal inflammatory disorders using QEESI©. Methods and Findings: Subjects were 261 outpatients who presented themselves for rhinologic evaluation. Subjects completed the QEESI© (Korean version) during the first visit. The prevalence rate of the very suggestive scores in all the rhinologic disease cases overall and CRS, NAR, and AR cases was examined and compared between each disease group. We compared the chief complaint and ARIA classification of AR with the degree of suggestive chemical intolerance. Of 261 patients, 45 patients (17.24%) were categorized into very suggestive of risk of chemical intolerance. The prevalence rate of very suggestive was higher in female (16.33%) than in male (9.82%). Among the CRS, NAR and AR groups, the number of very suggestive cases were 17 (18.47%), 4 (15.38%), and 11 (13.25) respectively and a statistical difference was not observed between each group (P>.05). When we compared the chief complaint according to the degree of severity, rhinorrhea and nasal obstruction was the chief complaint in the cases of very suggestive scores. Conclusions: We suggest that control of chemical intolerance can be helpful to treat nasal inflammatory disorders and QEESI© may be useful questionnaire for the screening of chemical intolerance in the nasal inflammatory disorders.